EFFECT OF SOWING DATES AND FERTILIZING NORMS ON BIOLOGICAL DRY MASS YIELD OF REPEATED SUNFLOWER VARIETIES - Ruzmanov Abdullo Norboy ugli (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article describes the accumulation of biological dry matter in sunflower varieties intended for secondary crop. Based on the results, the “Diyor” and “Jahongir” sunflower varieties have average dry matter of 81.0 and 155.3 q/ha, respectively.